2013
DOI: 10.2108/zsj.30.125
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Sex Differentiation in Frogs: How Testes Become Shorter than Ovaries

Abstract: Testis differentiation in anuran amphibians is the result of two opposing processes: degeneration of the distal part, and development of the proximal part, which becomes a functional male gonad. Undifferentiated gonad differentiates directly into a testis without a transition phase. We described the morphology of developing testes in Rana temporaria and Hyla arborea, and made careful histology and ultrastructure in Pelophylax lessonae. The developing testis was divided into 10 stages (I-III, undifferentiated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 26 publications
4
54
1
Order By: Relevance
“…During testis development the distal part gradually became reduced and disappeared. The final testis developed from 2-4 anterior gonomeres (Haczkiewicz and Ogielska 2013). The authors concluded that the testes shorten during development.…”
Section: Discussionmentioning
confidence: 97%
“…During testis development the distal part gradually became reduced and disappeared. The final testis developed from 2-4 anterior gonomeres (Haczkiewicz and Ogielska 2013). The authors concluded that the testes shorten during development.…”
Section: Discussionmentioning
confidence: 97%
“…Ovaries in common frogs develop from the whole gonadal primordia into a large whitish/yellowish structure with distinct lobes, and a characteristic granular aspect conferred by the many oocytes embedded in the cortex [31]. By contrast, testes develop from the anterior part of the gonadal primordia only (the posterior part degenerates) into a small oblong structure, with a smooth cortex covered with melanic spots [32]. In case of doubt, gonads were considered as undifferentiated and sex was not assigned (NA).…”
Section: Materials and Methods (A) Field Sampling And Husbandrymentioning
confidence: 99%
“…Ovaries in common frogs develop from the whole gonadal primordia into a large whitish/yellowish structure with distinct lobes, and a characteristic granular aspect conferred by the many oocytes embedded in the cortex (Ogielska and Kotusz, 2004). In contrast, testes develop from the anterior part of the gonadal primordia only (the posterior part degenerates) into a small oblong structure, with a smooth cortex covered by melanic spots (Haczkiewicz and Ogielska, 2013). In case of doubt, gonads were considered as undifferentiated and sex was not assigned.…”
Section: Frog Sampling and Pedigree Buildingmentioning
confidence: 99%